2020
DOI: 10.5007/2175-8069.2020v17n45p33
|View full text |Cite
|
Sign up to set email alerts
|

Estudo sobre a usabilidade das práticas de contabilidade gerencial mais intensamente usadas em empresas que atuam no Brasil

Abstract: Este estudo teve como objetivo principal investigar os principais atributos que caracterizam a usabilidade da Práticas de Contabilidade Gerencial mais intensamente usada por gestores de diferentes níveis funcionais em organizações que atuam no Brasil. As dimensões de usabilidade foram mensuradas a partir dos constructos definidos por Mahama e Cheng (2013), a saber: coercivo, habilitante, reparo, flexibilização, transparência interna e transparência global. O método de coleta de dados foi o survey, sendo enviad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
1
1
2
Order By: Relevance
“…On the other hand, when compared with the study by Souza and Lisboa (2018), a discrepancy is observed in relation to the pace of adoption of advanced managerial accounting practices. Souza and Lisboa's (2018) study suggests slower adoption, while our research indicates a more accelerated adoption trend, particularly in organizations operating in highly competitive and dynamic environments.…”
Section: Divergences From Similar Workcontrasting
confidence: 62%
“…On the other hand, when compared with the study by Souza and Lisboa (2018), a discrepancy is observed in relation to the pace of adoption of advanced managerial accounting practices. Souza and Lisboa's (2018) study suggests slower adoption, while our research indicates a more accelerated adoption trend, particularly in organizations operating in highly competitive and dynamic environments.…”
Section: Divergences From Similar Workcontrasting
confidence: 62%
“…Briefly, MA and AMP are seen as tangible realities (tools) found in organizations; they play previously set, clear and objective roles, despite differences observed in their use and performance, in different organizations and countries. Corporate budget ranks the first position among the most used AMPs in Brazil (Souza, Russo, & Guerreiro, 2020).…”
Section: Understanding the Controllership And The Accounting Manageme...mentioning
confidence: 99%
“…Em síntese, a CG considera PCG como realidades tangíveis (ferramentas), presentes nas organizações com papéis claros e objetivos previamente estabelecidos, apesar das diferenças encontradas em seu uso e desempenho em diferentes organizações e países. Entre as PCG mais utilizadas no Brasil, o orçamento empresarial está em primeiro lugar (Souza, Russo, & Guerreiro, 2020).…”
Section: Compreendendo a Controladoria E As Práticas De Contabilidade...unclassified